2002
DOI: 10.1177/1527002502003001002
|View full text |Cite
|
Sign up to set email alerts
|

Contract Length and the Return to Performance in Major League Baseball

Abstract: This article focuses on the relationship between contract length and compensation in Major League Baseball. Because the best players receive both the highest salaries and the longest contracts, wage regressions that omit length can lead to misleading inferences. Although contract duration is positively related with salaries, the authors find evidence of a negative relationship between contract length and a player’s return to performance. These results indicate some type of trade-off going on in the negotiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 10 publications
4
45
0
Order By: Relevance
“…Krautmann and Oppenheimer (2002) used free agents for their sample and found a positive correlation between contract length and salary, indicating that the players with the best performance not only obtained higher salaries, but also longer contracts. This study extends this analysis to players eligible for salary arbitration and players extending their current contracts.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Krautmann and Oppenheimer (2002) used free agents for their sample and found a positive correlation between contract length and salary, indicating that the players with the best performance not only obtained higher salaries, but also longer contracts. This study extends this analysis to players eligible for salary arbitration and players extending their current contracts.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…As a result, the negotiation of these contracts has become more important to the players than ever before. Krautmann and Oppenheimer (2002) found that contract length and salary have a positive correlation. Moreover, they also found a negative correlation between contract length and a player's return to performance-the longer the contract, the lower the return to performance.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations